Process Development, Nutrient and Sensory Qualities of Hot and Sweet Sauce with Tamarind (Tamarindus Indica L.) - Abdi, Sadiya Mohammed; Serrem , Charlotte Atsango (African Journal of Education,Science and Technology (AJEST), 2013)
Tamarind is a nutritious and drought resistant wild fruit that is underutilized in many countries of the world including Kenya. As one way of its utilization, a study was conducted to develop hot and sweet sauce, popular among many Kenyan communities using tamarind, determine its physic-chemical characteristics and evaluate its sensory acceptability among consumers. Three variations of hot and sweet sauce with none, 30% and 60% tamarind, respectively were formulated and developed. To establish the physico-chemical characteristics, proximate composition, acidity and viscosity were determined. Acceptability was evaluated using hedonic categorization on a 9-point scale and preference ranking by 50 University of Eldoret students who normally use chili. Compared to the sauce without tamarind, nutrient content increased in 60% addition of tamarind, by 39% protein, 17% ash and 6% fat. Viscosity also increased by 40%, while moisture and pH reduced by 65% and 28%, respectively. Sensory evaluation results showed that the sauce with 60% tamarind was rated highest for the attributes of texture, flavour, sweetness, hotness and overall acceptability. Additionally it scored highest on total quality (93%) and was the most preferred of the three variations by consumers. Addition of tamarind to hot and sweet sauce improves its nutrient content, physical characteristics and sensory properties. Further research should be conducted into incorporating tamarind into more Kenyan food products to improve nutrition and boost food security. Simple techniques to process mature tamarind pod for pulp to enhance its industrial use should be developed.